2020
DOI: 10.1038/s42003-020-0761-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of chimeric peptides to facilitate the neutralisation of lipopolysaccharides during bactericidal targeting of multidrug-resistant Escherichia coli

Abstract: Pathogenic Escherichia coli can cause fatal diarrheal diseases in both animals and humans. However, no antibiotics or antimicrobial peptides (AMPs) can adequately kill resistant bacteria and clear bacterial endotoxin, lipopolysaccharide (LPS) which leads to inflammation and sepsis. Here, the LPS-targeted smart chimeric peptides (SCPs)-A6 and G6 are generated by connecting LPS-targeting peptide-LBP14 and killing domain-N6 via different linkers. Rigid and flexible linkers retain the independent biological activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 69 publications
0
34
1
Order By: Relevance
“…To evaluate the effect of preparations, the samples (0.1 mL) were collected after 0, 15, 30, 45, 60, 120 and 240 min and were sown on LB agar to determine number of colonies after 16–18 h of incubation at 37 °C according to [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the effect of preparations, the samples (0.1 mL) were collected after 0, 15, 30, 45, 60, 120 and 240 min and were sown on LB agar to determine number of colonies after 16–18 h of incubation at 37 °C according to [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, we find it reasonable to assume that the previous fruitful findings and constructive theories from antibacterial studies with AMPs in vivo and in vitro, such as those concerning the mechanism of entry into the host cell and bactericidal details, might be shared and referenced during antiviral studies; it is confirmed from previous works that AMPs enter the blood circulation through different drug delivery routes, reach various organs, and further internalize into the cells through endocytosis and micropinocytosis [ 116 , 117 , 118 , 119 ]. Undoubtedly, wider and deeper new findings are highly deserving of anticipation and will attract great interest due to the unique advantages of AMPs, including their high penetration into the host cell owing to their intracellular origin, their close compatibility with the host, their hypersensitive early-warning/protection response to infection, and their low drug resistance rate owing to strong penetration and multitargeting of pathogens [ 30 , 120 , 121 , 122 , 123 , 124 , 125 ]. We strongly believe and optimistically expect that with the further elucidation of the structure, expression regulation, and mechanism of action of AMPs as a whole, the factors that limit the development of AMPs will be disclosed and overcome one by one, and more new functions of AMPs will be discovered.…”
Section: Discussionmentioning
confidence: 99%
“…The BC probe was used to determine the ability of peptides to bind to LPS [ 54 ]. A total of 0.5 µM LPS was incubated with 5 μM BC in 50 µM Tris buffer (pH 7.4) for 4 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%